Legal Review of Inclusive Education Policy: A Systematic Literature Review 2015-2025 - Kartiko, Ari; Arif, Muhamad; Rokhman, Mauhibur; Ma’arif, Muhammad Anas; Aprilianto, Andika (NAJAHA, 2025)
Inclusive quality education is essential for national development, aligning with Indonesia's goal to educate intelligent, responsible, and noble citizens without discrimination. Binding legal regulations become the basis for implementing inclusive education that is fair and without prejudice. As for these two research questions: how are the legal rules governing inclusive education in Indonesia and other countries? What are the challenges of implementing inclusive education in Indonesia? Using the systematic literature review research method, with keywords in Indonesian and English,